Postmodernity and Christian Humanism - Fisichella, Rino (Cuestiones Teológicas, 2011)
Where is the starting point to think over christian humanism? What is the role that should play the concept of natural law in christian humanism? These are the questions stated in this article by Dr. Fisichella. He starts his narrative by dealing wich the changing of time wich could be represented by this momento in history; ¿what does it mean? (an end or a a beginning?).The autor approaches the concern of “choosing rights à la carte” and, after going through this notion and its developments, he proposes the concept of natural law as a basis for his reflection.
Keywords: Humanism; Natural Law; Christian Humanism; Ethics; Postmodernity